2018
DOI: 10.1007/s10461-018-2123-4
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Motivations for Marijuana Use in HIV-Positive and HIV-Negative Adults

Abstract: While medicinal marijuana use is common among persons with HIV, it is not known whether persons with HIV are more motivated to use marijuana medically compared to HIV-negative counterparts. This study examined motivations for marijuana use in a sample of 94 HIV+ and HIV- adults. Participants used marijuana 21.27 days in the last 30 days on average. HIV+ participants reported using marijuana for medical reasons more often than HIV- participants, but HIV+ and HIV- participants did not differ in other domains. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Despite research pointing to high rates of daily cannabis use among HIV+ YMSM, relatively little research has examined the different motives for cannabis use within this population. Although previous research on cannabis motives has assumed a recreational taxonomy of use (Simons et al 1996;Zvolensky et al 2007), emergent findings comparing HIV-positive and HIV-negative adult users have found that PLWH are less likely to report recreational motives as their primary reason for current cannabis use (Towe et al 2018). In the same study, among persons who selected medical use as their primary reason for using cannabis, PLWH scored significantly higher than HIV-negative users on social and expansion motives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite research pointing to high rates of daily cannabis use among HIV+ YMSM, relatively little research has examined the different motives for cannabis use within this population. Although previous research on cannabis motives has assumed a recreational taxonomy of use (Simons et al 1996;Zvolensky et al 2007), emergent findings comparing HIV-positive and HIV-negative adult users have found that PLWH are less likely to report recreational motives as their primary reason for current cannabis use (Towe et al 2018). In the same study, among persons who selected medical use as their primary reason for using cannabis, PLWH scored significantly higher than HIV-negative users on social and expansion motives.…”
Section: Discussionmentioning
confidence: 99%
“…Ethnographic research has divided recreational cannabis adult users into two groups: those that use to enhance relaxation and those that use also to enhance concentration (Osborne & Fogel 2008). Recent findings have reported adults living with HIV using cannabis for mental health and socialization and expansion motives in tandem with medical use and symptom management (Towe et al 2018). The degree to which recreational motives, such as enhancement, expansion, or socialization, may align or map onto medically-oriented motives for cannabis use among HIV+ YMSM has not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…As psychoactive substance use is highly prevalent in HIV-HCV co-infected patients [12][13][14][15], we may expect HCV cure to impact substance use behavior. The benefits of cannabis and cannabinoid use for HIV infection management and less severe treatment side-effects, are widely recognized [16,17], and PLWH frequently report their therapeutic use [18][19][20][21][22]. However, cannabis use may also promote pulmonary disease [23] and cognitive impairments in PLWH [24].…”
Section: Introductionmentioning
confidence: 99%
“…The other half used community samples, but generally young adults in the early- to mid-twenties. Only 2 studies reported an average age of 30 or older 22 , 23 and both recruited from specialized locations.…”
Section: Introductionmentioning
confidence: 99%